The Analysis Impact of Irrigation Channel on Rice Production in Bendosari, Sukoharjo Regency - Naufal Sauqi; Agus Anggoro Sigit; Jumadi (International Journal for Disaster and Development Interface, 2021)
The irrigation network infrastructure development and rehabilitation program has several targets to be achieved including the construction and improvement of the 9.89 million ha irrigation network, and the rehabilitation of the surface irrigation network, covering 3.01 million ha. The program for adding and repairing irrigation networks is expected to be able to realize food self-sufficiency that has been declared by the Indonesian government. The method used is a field survey. The survey method aims to obtain a general description of the object or target in this study. The variable used is the amount of rice farmland production each year based on the potential of agricultural land and irrigation canal damage. The results of the calculation of estimated rice production in Sukoharjo Regency in 2018 were 400574.62 tons. High potential rice field productivity class with 2-3 times the amount of harvest per year has the most production that is 220,327.52 tons. Potential factors of paddy farming land and the number of harvests in one year greatly affect the productivity of rice plants, while damage to irrigation channels is slightly damaged and moderate does not affect rice productivity.